Interfacial chemistry and reinforcement mechanisms of polyurethane composites via epoxy-modified fly ash - Xu Li; Mingyi Li; Peiyu Jia; Sitong Zhang; Lan Jia; Zhiyi Zhang; Fengbo Zhu; Wenwen Yu (Polymer Testing)
The recycling of coal-based solid waste, particularly fly ash (FA), is crucial for sustainable resource utilization. Interfacial incompatibility limits FA use in polymer composites. This study resolves this issue by tailoring FA surface chemistry using three epoxy-functionalized silane agents (KH-186, KH-560, KH-562). The KH-560-modified FA achieved ∼45 % higher mechanical strength (compressive, tensile, lap shear) and 64.5 % enhanced interfacial bonding in polyurethane (PU) composites compared to unmodified FA. The comprehensive analysis of microstructure, interfacial energy and cross-linking degree of the composite revealed two critical factors: (1) hydrolyzable group density (not type) dominated interfacial wettability, as incomplete hydrolysis of KH-562 increased residual hydroxyl groups, causing polarity mismatch with the PU matrix; (2) steric hindrance from epoxy-linked groups reduced epoxy reactivity, weakening covalent bonding with PU isocyanates. KH-560's structural optimization, maximizing alkoxy groups while minimizing steric effects, enabled robust epoxy-NCO bonding and efficient stress transfer. Adhesion tests confirmed KH-560's superiority, outperforming KH-550 by 10∼30 % across substrates. This work establishes a novel design principle for silane coupling agents, prioritizing hydrolyzable group density and steric control, to transform FA into high-performance filler. By linking interfacial engineering with sustainable waste recycling, the findings offer scalable solutions for applications requiring superior adhesion, advancing both material science and circular economy goals.